Apple (Malus domestica Borkh.) seed: A review on health promoting bioactivities and its application as functional food ingredient. (December 2022) - Kumar, Manoj; Barbhai, Mrunal D.; Esatbeyoglu, Tuba; Zhang, Baohong; Sheri, Vijay; Dhumal, Sangram; Rais, Nadeem; Radha; Said Al Masry, Eman Mohammad; Chandran, Deepak; Pandiselvam, Ravi; Senapathy, Marisennayya; et al.
Abstract: Recent trends in food industry focus on utilization of fruit processing waste and by-products as novel ingredients due to their nutritional benefits. Apple seed is one such novel ingredient that can find application as functional ingredient in food, nutraceutical and pharmaceutical industry. The existing studies suggest that apple seed is a rich source of amino acids, fatty acids and polyphenolic compounds. This review discusses the nutritional and phytochemical profile as well as biological activities exhibited by the apple seed. It also highlights the current application of apple seed in food, pharmaceutical and nutraceutical industries along with the safety aspects considering the presence of amygdalin. The apple seed meal, extracts or seed oil as novel ingredient can find various industrial applications given their dense nutritional profile. Besides their functionality, rigorous and extensive research is required to promote its usage at industrial level for harnessing the benefits of apple seeds. Highlights: This is pioneering work on reviewing phytochemical profile and biological activities of apple seed. Apple seed is a superior source of bioactive compounds. Apple seed extracts display cardioprotective, antidiabetic, & anticancer activities. Antioxidant and antimicrobial activities make apple seed suitable for use in foods.